2017
DOI: 10.14814/phy2.13000
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-releasing hormone improves survival in pneumococcal pneumonia by reducing pulmonary inflammation

Abstract: The use of glucocorticoids to reduce inflammatory responses is largely based on the knowledge of the physiological action of the endogenous glucocorticoid, cortisol. Corticotropin‐releasing hormone (CRH) is a neuropeptide released from the hypothalamic–pituitary–adrenal axis of the central nervous system. This hormone serves as an important mediator of adaptive physiological responses to stress. In addition to its role in inducing downstream cortisol release that in turn regulates immune suppression, CRH has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…Limited information is available on how targeting CRH and CRHR activity in the respiratory tract impacts bacterial disease outcome. In a murine respiratory Streptococcus pneumoniae infection model, Burnley and Jones (2017) demonstrated that intranasal CRH administration reduces the pulmonary inflammatory response, and the subsequent recruitment of neutrophils and monocytes to the lung, improving survival in these animals ( 43 ). Moffat et al (2006) demonstrated that, urocortin, a structurally related peptide to CRH, causes bronchorelaxation and limits lipopolysaccharide (LPS)-induced pulmonary inflammation (specifically neutrophil recruitment) to a greater extent than CRH ( 44 ).…”
Section: Central Endocrine (Hypothalamic and Pituitary) Hormonesmentioning
confidence: 99%
“…Limited information is available on how targeting CRH and CRHR activity in the respiratory tract impacts bacterial disease outcome. In a murine respiratory Streptococcus pneumoniae infection model, Burnley and Jones (2017) demonstrated that intranasal CRH administration reduces the pulmonary inflammatory response, and the subsequent recruitment of neutrophils and monocytes to the lung, improving survival in these animals ( 43 ). Moffat et al (2006) demonstrated that, urocortin, a structurally related peptide to CRH, causes bronchorelaxation and limits lipopolysaccharide (LPS)-induced pulmonary inflammation (specifically neutrophil recruitment) to a greater extent than CRH ( 44 ).…”
Section: Central Endocrine (Hypothalamic and Pituitary) Hormonesmentioning
confidence: 99%